Art as medicine creating a therapy of the imagination - McNiff, Shaun
""Whenever illness is associated with loss of soul," writes Shaun McNiff, "the arts emerge spontaneously as remedies, soul medicine." The medicine of the artist, like that of the shaman, arises from his or her relationship to "familiars"—the themes, methods, and materials that interact with the artist through the creative process. Art As Medicine demonstrates how the imagination heals and renews itself through this natural process. The author describes his pioneering methods of art therapy—including interpretation through performance and storytelling, creative collaboration, and dialoguing with images—and the ways in which they can revitalize both psychotherapy and art itself."--